2014
DOI: 10.5539/ijb.v6n3p46
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Anabasine and the Alkaloid Extract of Nicotiana glauca on Lepidopterous Larvae

Abstract: For several decades, Nicotiana glauca has been known for its content of the pyridine alkaloid, anabasine. The toxicological effects of this metabolite have been extensively studied, as opposed to its potential insecticidal activity. The anabasine content of leaves of N. glauca, collected from Malta, was 0.258 ± 0.0042% as determined by High Performance Liquid Chromatography. In the Pieris rapae larval bioassay, the median effective concentrations of anabasine and the alkaloid extract were 0.572 and 1.202 mg pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…These included anabasine and several highly abundant sugars. Anabasine is an alkaloid that is a structural isomer of nicotine and is known to be similarly toxic to insects (Zammit et al, 2014). Thus, we wanted to account for the effects of mutations in wax-related genes on the abundance of this metabolite in the mutants.…”
Section: Exploiting a Set Of Cuticular Wax Mutants To Study Plant-herbivore Interactionsmentioning
confidence: 99%
“…These included anabasine and several highly abundant sugars. Anabasine is an alkaloid that is a structural isomer of nicotine and is known to be similarly toxic to insects (Zammit et al, 2014). Thus, we wanted to account for the effects of mutations in wax-related genes on the abundance of this metabolite in the mutants.…”
Section: Exploiting a Set Of Cuticular Wax Mutants To Study Plant-herbivore Interactionsmentioning
confidence: 99%
“…Anabasine is quoted to be a very toxic alkaloid not solely to insects. 21 Concerning to the estimated amount of money lost due to the damage by Nicotiana glauca per year, 35% the respondents did not recognized its impacts, 28.3% reported as if it was difficult to estimate and insignificance number of the respondents (5.1%) reported as 8000_15,000 Ethiopian Birr. Regarding the level of negative impact of Nicotiania glauca on biodiversity, majority of the respondents (66.6%)reported that the negative impact of Nicotiania glauca on biodiversity increase slightly and sharply and 31.7 % of the respondents stated as remained constant whereas insignificant number of the respondents (1.7%)indicated that the negative impact of Nicotiana glauca decreased slightly (Table 3).…”
Section: Impact Of Nicotiana Glaucamentioning
confidence: 99%
“…Anabasine and nicotine exert their insecticidal effect by interacting with nicotinic acetylcholine receptors [222,223]. Anabasine and Nicotiana glauca extracts were tested for their effects against Pieris rapae larvae [216]. The paralysis of the larvae was an indicator of activity.…”
Section: Conclusion and Further Directionsmentioning
confidence: 99%
“…Nicotine predominated in Nicotiana tabacum [213] and Nicotiana rustica [214] whereas anabasine predominates in Nicotiana glauca [214,215]. The leaves of Maltese Nicotiana glauca were dried and extracted with 200ml of 0.5% sodium hydroxide [216]. After volume reduction, chloroform was added to extract the alkaloids in this organic phase.…”
Section: Nicotiana Glauca Rc Grahammentioning
confidence: 99%
See 1 more Smart Citation